Operative Training Programmes in India - Central Institute of Fisheries Operatives (Fishery Technology, 1966)
During the last few years great changes have taken place in the fishing industry as a result of which production of fish in the world has increased enormously. From an insignificant trade employing tools and methods of primitive nature, fishing in many countries has become an important industry utilizing complex modern vessels equipped with electronic equipment and operating in the high seas with highly mechanized fishing gear.